2020
DOI: 10.1007/s40995-020-00974-5
|View full text |Cite
|
Sign up to set email alerts
|

Biased Adjusted Poisson Ridge Estimators-Method and Application

Abstract: Månsson and Shukur (Econ Model 28:1475–1481, 2011) proposed a Poisson ridge regression estimator (PRRE) to reduce the negative effects of multicollinearity. However, a weakness of the PRRE is its relatively large bias. Therefore, as a remedy, Türkan and Özel (J Appl Stat 43:1892–1905, 2016) examined the performance of almost unbiased ridge estimators for the Poisson regression model. These estimators will not only reduce the consequences of multicollinearity but also decrease the bias of PRRE and thus perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Following Månsson and Shukur 3 and Qasim et al, 8 we suggest the following biasing parameters for the PRR, RPRR, PAUR, and RPAUR estimators: The suggested truek^$$ \hat{k} $$ for the PRR estimator is ktrue^PRRgoodbreak=maxtrueα^j2j=1p+1.$$ {\hat{k}}_{PRR}=\max {\left(\sqrt{{\hat{\alpha}}_j^2}\right)}_{j=1}^{p+1}. $$ The suggested truek^$$ \hat{k} $$ for the RPRR estimator is ktrue^RPRRgoodbreak=maxtrueα^j*2j=1p+1.$$ {\hat{k}}_{RPRR}=\max {\left(\sqrt{{\hat{\alpha}}_j^{\ast 2}}\right)}_{j=1}^{p+1}.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Månsson and Shukur 3 and Qasim et al, 8 we suggest the following biasing parameters for the PRR, RPRR, PAUR, and RPAUR estimators: The suggested truek^$$ \hat{k} $$ for the PRR estimator is ktrue^PRRgoodbreak=maxtrueα^j2j=1p+1.$$ {\hat{k}}_{PRR}=\max {\left(\sqrt{{\hat{\alpha}}_j^2}\right)}_{j=1}^{p+1}. $$ The suggested truek^$$ \hat{k} $$ for the RPRR estimator is ktrue^RPRRgoodbreak=maxtrueα^j*2j=1p+1.$$ {\hat{k}}_{RPRR}=\max {\left(\sqrt{{\hat{\alpha}}_j^{\ast 2}}\right)}_{j=1}^{p+1}.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, authors have adopted and modified new approaches to estimating the biasing parameter k , which is given in many studies. For more details, see Månsson and Shukur, 3 Türkan and Özel, 7 and Qasim et al 8 …”
Section: Introductionmentioning
confidence: 99%
“…There are several methods to estimate the shrinkage parameter (see, e.g. [16][17][18][19][20][21]). Unlike linear regression, the effect of multicollinearity on GLM has not significantly been discussed in the literature using ridge regression approach.…”
Section: Introductionmentioning
confidence: 99%
“…Exceptionally, Månsson and Shukur [22] introduced some ridge parameters for the logistic regression model, Månsson and Shukur [23] established a Poisson ridge regression (PRR) estimator. Since PRR can have a severe bias, Qasim et al [20] suggested bias adjusted PRR estimators. Amin et al [19] examined the performance of inverse Gaussian ridge regression estimators.…”
Section: Introductionmentioning
confidence: 99%
“…e Liu estimator is an ace in this regard as it avoids the disadvantages of the ridge estimator [10], where the main advantage of the ridge is easy to use, and it can be written in the explicate and the objective formulas. In the literature, various studies are available for the PRM to overcome the presence of collinearity [7,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%